(3eGdjI GdOhdI (B/s - (3GdYdj, YGOd adjMs ((3YeGf(B: s (3OGQRgQGf(B, s, 2008)
(3WHjYI h fWGb Yde GdeGdjI GdYGeI , JWhQ GdeGdjI GdYeI , eGgjI GdfabGJ GdYGeI h MLe gPg GdfabGJ , JbSje GdfabGJ GdYGeI , XGgQI GdJRGjO GdeSJeQ ddfabGJ GdYGeI , GdBKGQ GdGbJUGOjI ddGfaGb GdYGeI , EjQGOGJ GdOhdI ef GedGcgG , GdQSe , GdVQGFH , GdbQhV GdYGeI , GdGUOGQ GdfbOj GdLOjO , GdEYGfGJ , GdJYQja HGdehGRfI GdYGeI ddOhdI , eHGOF GdehGRf h bhGYOgG , JMVjQ GdehGRfI h GYOGOgG , JfajP GdehGRfI h eJGHYJgG , GdQbGHI Ydi JfajP GdehGRfI GdYGeI ddOhdI (B.s
Keywords: (3GdeGdjI GdYGeIs